A Review of Vibration Control Studies of Double-Layered Cylindrical Shells Under Transient Excitation in Water - Zhen Zhang; Yinglong Zhao; Feng Chen (Journal of Marine Science and Engineering)
In recent years, with the wide application of underwater vehicles, the vibration and noise problems generated during their operation have attracted great attention from the academic community. Compared with the field of traditional mechanical noise, research on vibration control of the noise that is transiently excited underwater still has significant deficiencies in terms of its theoretical depth and systematicity. In this paper, we take transient noise control for underwater vehicles as the engineering entry point; systematically explain the vibration mechanisms and dynamic characteristics of underwater double-layered cylindrical shell structures; and discuss the vibration transmission paths and the development trends in the control technology in depth. This study mainly includes the following contents. Firstly, the vibration response mechanisms of underwater double-layered cylindrical shells are sorted through a bibliometric analysis, and the evolution laws for plate–shell structures and the vibration transmission paths for single–double-shell structures are summarized systematically; secondly, the multi-path vibration transmission characteristics of double-layered cylindrical shells are analyzed based on energy transfer theory, and the contribution to transient noise through different transmission paths is quantitatively evaluated; and thirdly, the vibration transmission characteristics of active control, passive control, and hybrid control are evaluated systematically in terms of the dimensions of the control mechanism. Then, the engineering applicability of active, passive, and hybrid control technologies is systematically reviewed. Finally, combined with the development of new intelligent materials and adaptive algorithms, the prospective outlook for vibration control technology for shell structures under transient excitation conditions is presented.